Penyelesaian Sengketa Adat Berbasis Lima Bassiq Dalam Masyarakat Hukum Adat Adolang di Kabupaten Majene - Sulastri Yasim; Andi Tamaruddin; Patly Parakkasi (Jurnal Interpretasi Hukum, 2025)
The Lima Bassiq serves as the guiding principles of life for the Adolang Indigenous Law Community in Majene Regency, rooted in the values of tutu bali-wali (considering humanity), saqbi bali-wali (openness), oro bali-wali (deliberation), palalo bali-wali (justice), and mammakkoq di gau tongan (doing good deeds). These principles form the foundation for customary dispute resolution and have been formally recognized through Majene Regent Decree No. 100.3.3.2/X/2024 concerning the Recognition and Protection of the Adolang Indigenous Law Community, mandated by Article 8 paragraph (2) of Majene Regency Regional Regulation No. 1 of 2023 on the Recognition, Protection, and Empowerment of Indigenous Law Communities. This study aims to examine dispute resolution mechanisms based on the Lima Bassiq, analyze their relevance within the framework of national law, and situate them within the perspective of restorative justice. Employing an empirical legal research method, this study integrates the analysis of official documents, literature on customary law, and interviews with traditional leaders. The findings reveal that the Lima Bassiq effectively preserves social harmony through dispute resolution mechanisms oriented toward restoring relationships, aligning with restorative justice policies under positive law.